Pan-Cancer Analysis Reveals That E1A Binding Protein p300 Mutations Increase Genome Instability and Antitumor Immunity - Chen, Zuobing; Chen, Canping; Li, Lin; Zhang, Tianfang; Wang, Xiaosheng (Frontiers in Cell and Developmental Biology, 2021)
EP300 is mutated in diverse cancers. Nevertheless, a systematic investigation into the associations of EP300 mutations with genome instability and anti-tumor immunity in pan-cancer remains lacking. Using the datasets from The Cancer Genome Atlas, we analyzed the correlations between EP300 mutations and genome instability and anti-tumor immune response in 11 cancer types. Compared to EP300-wildtype cancers, EP300-mutated cancers had significantly higher tumor mutation burden (TMB) in 10 cancer types. EP300-mutated cancers harbored a much higher fraction of microsatellite instable cancers in the colon and gastric cancers. EP300 was co-mutated with genes involved in DNA damage repair pathways in multiple cancers. Furthermore, compared to EP300-wildtype cancers, EP300-mutated cancers had significantly higher immune cytolytic activity scores and ratios of immune-stimulatory over immune-inhibitory signatures in diverse cancers. Also, EP300-mutated cancers showed significantly higher PD-L1 expression levels than EP300-wildtype cancers. The increased TMB, anti-tumor immune activity, and PD-L1 expression indicated a favorable response to immune checkpoint inhibitors (ICIs) in EP300-mutated cancers, as evident in three cancer cohorts treated with ICIs. Thus, the EP300 mutation could be a predictive biomarker for the response to immunotherapy.